(NwWEDENIE W GRUBYE SISTEMY DIFFERENCIALXNYH URAWNENIJ (B:s (Nu^EBNOE POSOBIE (B/s - (NpIL@GIN(B, (NsERGEJ `RXEWI^s ((Nl(B. :s (Nlgu(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 156-157 (42 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 158-159s
Keywords: (NdIFFERENCIALXNYE URAWNENIQs